The Effect of a Problem-Based Learning Model Assisted by Augmented Reality on the Computational Thinking Skills of Grade XI Students at SMAN 1 Labuapi - Diyah Nurmayanti; Mahrus Mahrus; Sambrean Akram; Roshiya Hilyatiy; Wilia Lara Ervantira (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2026)
The rapid development of science and technology requires students to possess computational thinking skills as part of 21st-century competencies. This study aims to determine the effect of the Problem-Based Learning model assisted by Augmented Reality on the computational thinking abilities of grade XI students. This research employed a quasi-experimental design with a nonequivalent control group, involving experimental and control classes at SMAN 1 Labuapi. The results showed that the average pretest scores of the experimental and control classes were relatively similar (45.20 and 46.80), while the posttest results indicated a significant improvement in the experimental class (74.50) compared to the control class (58.30). Hypothesis testing confirmed that the implementation of Problem-Based Learning, assisted by Augmented Reality, had a significant effect on students’ computational thinking skills, as evidenced by higher corrected mean scores in the experimental class (67.620) than in the control class (46.130). In conclusion, integrating Problem-Based Learning with Augmented Reality effectively enhances students’ computational thinking abilities. This study suggests that innovative learning models integrated with technology can be used to improve higher-order thinking skills in biology.